Physical performance status predicts mortality in aging patients undergoing pacemaker implantation. Issue 10 (October 2021) - Balla, Cristina; Passarini, Giulia; Bonsi, Beatrice; Pavasini, Rita; Tonet, Elisabetta; Malagú, Michele; Campo, Gianluca; Bertini, Matteo
Abstract : Aims: To assess whether frailty or reduced physical performance status may have an impact on clinical outcomes after pacemaker implantation in aging patients. Methods: A prospective cohort of patients aged more than 70 years, admitted to the hospital for pacemaker implantation, was enrolled. Patients were evaluated with the Short Physical Performance Battery (SPPB) and Handgrip Strength Test at hospital discharge and at 1 year. Overall mortality was the primary study endpoint. Results: Out of the 119 patients, the majority (71%) of patients had reduced physical performance (defined by an SPPB score <10 points). After a median follow-up of 46 months, the mortality was 31% of the population. SPPB value at discharge predicted death even after adjusting for pertinent confounders (adjusted hazard ratio 0.91, 95% confidence interval (CI) 0.84–0.99, P = 0.02). Patients with a poorer SPPB score at discharge (SPPB 0–3) had also an increased risk of death or rehospitalization at 1 year compared with patients with highest SPPB score (odds ratio OR 4.05, 95% CI 1–16.6). Conclusion: Reduced physical performance is associated with increased mortality in aging patients with bradyarrhythmia requiring pacemaker implantation. The identification of patients with poor SPPB may tailor specific interventions to improve physical performance and outcomes after pacemaker implantation. The trial was registered in clinicaltrial.gov with the identifier NCT02386124